PARADIGM CONTESTATION IN NATIONAL LEGAL SYSTEM: A STUDY OF UNIFICATION OF MARITAL AGE REGULATION IN INDONESIA - Khaidarulloh Khaidarulloh (JARES (Journal of Academic Research and Sciences), 2020)
This article focuses on the study of the unification of marital age in Indonesia with the contestation of legal paradigms that occur, both on the government side through legislators and on non-government parties such as the influence of religious ideology or the role of other humanitarian activists. The issue of marital age is not a dynamic issue, either juridical or sociological problems are strongly reflected in the discourse that has developed to date. The results of the study show that even though marital age has been compared to the new rules through Law No. 16 of 2019 stating that the minimum marital age for the bride and groom is 19 years, yet the potentials of the legal paradigm contestation in the national marriage legal system will always develop along with the social dynamics of the community.